Grain Yield and Yield Related Traits of Bread Wheat as Influenced by N and Seeding Rates and Their Interaction Effects in 2020 under Irrigation at Western and North of Oromia, Ethiopia - Hailu Feyisa; Girma Mengistu; Alemayehu Biri; Temesgen Chimdessa (International Journal of Agronomy)
Wheat is among the cultivated and important crops in Ethiopia because of its high value as a stable food that is mostly grown under rain-fed conditions. Even though the country has the potential to produce a sufficient amount of wheat grain under rain-fed and by using irrigation, the country still depends on importing wheat grain every year. Soil fertility depletion, inappropriate agronomic practices, erratic rainfall, and drought are among the constraints to the low yield of wheat crops in the country. In view of this, the field experiment was conducted during the off-season of 2020 in five districts, namely, Horo, Jimma Geneti, Jimma Arjo, Wayu Tuka, and Degem districts that are selected as representatives in terms of agricultural production and irrigation potential. The treatments consisted of five N fertilizer levels (0, 23, 46, 69, and 92 kg·ha−1) and three seeding rates (125, 150, and 175 kg·ha−1) of bread wheat, which constituted a total of 15 treatments. The experiment was laid out in a randomized complete block design with a factorial arrangement in three replications. The plot size was 3 m × 5 m. From the study, we observed that the grain yield and yield components of wheat were improved by optimizing nitrogen application and plant population. Maximum grain yield of 6.8, 8.9, 4.1, 4.8, and 2.5 t·ha−1 was recorded in response to the use of 92/125, 23/150, 23/150 and 175, 69/150, and 69/175 kg·ha−1 N/seed rate of wheat under irrigation condition in Horo, Jimma Geneti, Jimma Arjo, Wayu Tuka, and Degem districts, respectively. On the contrary, the lowest yield was observed from the unfertilized plot that was planted at 125 kg·ha−1 seed rate in all districts, except in Jimma Geneti, which was observed at 0/150 kg·ha−1 N/seed rate. The differences in yield between districts are mainly attributed to the variability in their soil-plant nutrient contents. Thus, N fertilizer and seed rates at 23/150, 69/150, 46/50, and 92/125 kg·ha−1 in Jimma Arjo and Jimma Geneti, Wayu Tuka, Degem, and Horo districts, respectively, gave maximum yield and net benefit with acceptable marginal rate of return, and it is economically feasible and the best rate to use by the end-users in bread wheat production under irrigation condition in the study area and agro-ecologies that are similar to the study area.